Rapid Initiation of Antiretrovirals in Two Newly Diagnosed HIV-infected Infants. Issue 1 (January 2017) - Clarke, Diana F.; Yildirim, Inci; Cooper, Ellen R.
Abstract : We report our experience with 2 infants with in utero HIV-1 infection who began very early combination antiretroviral therapy within 4 hours of birth. Further neonatal studies of antiretroviral pharmacokinetics (PKs), safety, efficacy and treatment strategies are critically needed for the development of more potent regimens for use in HIV-infected infants.